Academic achievement and self-regulated learning from parent’s perspective of student with learning difficulties - Ayed Hanna Ziadat; Mohammad Abed Sakarneh (Institute of Advanced Engineering and Science, 2022)
The study was designed to realize the association between academic achievement and self-regulated learning of students presenting learning difficulties. Therefore, the study adopted a quantitative approach and distributed the developed questionnaire to over 384 participants. The results reported underscored worsen achievement of students in distance learning compared to face-to-face setting despite the assistance they received during distance settings. The achievement of students differs due to the category of difficulty. Students presenting learning difficulties exhibited medium acquisition level of self-regulated learning. Elementary stage students exhibited a higher level of self-regulated learning, while female students exhibited a higher level of self-efficacy, metacognitive, micro-strategies, and emotional support. There is a strong association combined between students’ achievement and self-regulated learning. Furthermore, the study revealed a difference in self-regulated learning due to students’ gender, difficulty categories, and grade. Future studies can opt for specific self-regulated learning strategies according to subjects' particularism, such as mathematic material or specific age groups using the self-assessment tool.